THE IMPLEMENTATION OF TEACHING ENGLISH USING EMERGENCY TEACHING PROGRAM DURING COVID-19 PANDEMIC AT SMP NEGERI 4 KEDIRI - Wulandari, Mahesi Rina; Setyawati, Lely; Amroni, Agus (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
This research was motivated by a phenomenon that occurred regarding the implementation of teaching English at the junior high school level during the Covid-19 pandemic at SMP Negeri 4 Kediri, which in the school the learning process had used the emergency teaching program, namely learning carried out online based on emergency curriculum guides. Descriptive qualitative methods are used in this research. Twenty resource persons were taken consisting of four English teachers at SMP Negeri 4 Kediri, one curriculum representative and five students from grades seven to ninth. The data collection in this research was carried out by interviews, observation and documentation and using three instruments there are interview guides, observation checklists, and list of documentation. The results of this research are: 1) The implementation of English teaching using the emergency teaching program at SMP Negeri 4 Kediri consists of three stages, namely planning which includes making lesson plans, syllabus, learning media, semester programs and annual programs; 2) the obstacles in the implementation of teaching English using the emergency teaching program during the Covid-19 pandemic at SMP Negeri 4 Kediri are the delay of students in collecting assignments, the difficulty of students understanding the material being taught, lack of self-confidence, assumptions regarding the difficulty of learning English (internal factors) and namely the lack of parental support for children, not all students have smart phones, and limited funds to buy quotas (external factors). 3) How to overcome the obstacles in implementation of teaching English using the emergency teaching program during the Covid-19 pandemic at SMP Negeri 4 Kediri are providing cell phone assistance to underprivileged students, increasing discipline in collecting assignments, namely by giving sanctions if they are late in collecting assignments.